The Effects of the Price Change, on the Demand of Agricultural Products During Summer Time - SULI, Dudi; Xhabija, Gjergji (European Journal of Sustainable Development, 2013)
A fall in the price of a good has two effects. First, consumers enjoy an increase in realpurchasing power, they are better of because can buy the same amount of the good forless money, and thus have money left overfor additional purchases. The will tend toconsume more of the good that has became cheaper and less of those goods that are nowrelatively more expensive. Both effects happen simultaneously, but it will be useful todistinguish between them in our analysis. The Demand Functionand Slutsky Equationduring the summer time in our products,tomato and cucumber confirms the economictheory of chain effect in the agricultural products. Our research is based to the face-to-face questions about the prices that consumersreceive, and to the theoretical approach toidentify these effects. The demand function for this product gives us the solution of howindividual’s utility-maximizing choices respondto changes in income and in the prices oftomatoes and cucumbers.